Xianglian Zhixie Tablet Antagonizes Dextran Sulfate Sodium-Induced Ulcerative Colitis by Attenuating Systemic Inflammation and Modulating Gut Microbiota - Li Y; Wang T; Ma B; Yu S; Pei H; Tian S; Tian Y; Liu C; Zhao X; Zuo Z; Wang Z (Dove Medical Press, 2023)
Yilin Li,1,* Tingting Wang,2,* Beibei Ma,2 Shangyue Yu,1 Hailuan Pei,1 Shiqiu Tian,1 Yingying Tian,1 Chuang Liu,1 Xinyue Zhao,1 Zeping Zuo,2 Zhibin Wang1,2 1School of Chinese Pharmacy, Beijing University of Chinese Medicine, Beijing, People's Republic of China; 2Beijing Tongrentang Technology Co., LTD. Pharmaceutical Factory, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhibin Wang; Zeping Zuo, Beijing Tongrentang Technology Co., LTD. Pharmaceutical Factory, No. 20S 3rd Ring Road Middle, Beijing, 100071, People's Republic of China, Email wangzhibin4804@126.com; zepingzuo@126.comPurpose: Xianglian Zhixie Tablet (XLZXT), a classical traditional Chinese medicine formulation, is commonly used to treat Ulcerative Colitis (UC) in China. However, the therapeutic mechanisms of XLZXT for UC have yet to be fully understood. This study aimed to investigate the curative benefits of XLZXT and its associated mechanisms for healing UC in mice.Methods: In the present study, the 1% dextran sulfate sodium (DSS) solution was used to establish the UC model in C57BL/6N mice. To investigate the therapeutic effects of XLZXT on DSS-induced UC mice, several parameters were measured, including DAI score, colon length, spleen index, pathological changes in colon tissue, and levels of inflammatory factors in plasma and colon tissue. By investigating the gut microbiota, assessing the levels of intestinal mucosal protein expression, and looking at the proteins involved in the TLR4/MyD88/NF-B p65 signaling pathway, the mechanisms of XLZXT impact on UC were investigated. Mouse feces were examined for patterns of gut microbiota expression using high-throughput sequencing of 16S rRNA.Results: XLZXT effectively alleviated UC symptoms and colon pathological damage in DSS-induced UC mice. It improved body weight loss, stool consistency, and hematochezia, while also repairing colon damage. Moreover, it down-regulated pro-inflammatory cytokines (such as TNF-α, IL-1β, and IL-6), and up-regulated anti-inflammatory cytokines (such as IL-10). XLZXT also increased the expression of MUC-2, Occludin and ZO-1, while decreasing the expression of NF-κB, MyD88 and TLR4. Additionally, it regulated gut microbiota disorder by increasing the abundance of beneficial bacteria and reducing the adhesion of intestinal harmful bacteria.Conclusion: XLZXT demonstrated therapeutic effects on DSS-induced UC mice. The mechanisms may be associated with repairing the intestinal mucosal barrier, regulating the TLR4/MyD88/NF-κB p65 signaling pathway, and restoring the balance of gut microbiota.Plain Language Summary: This is the first study to probe the therapeutic potential of XLZXT for UC. Our findings indicated that XLZXT could effectively alleviate the clinical symptoms of UC and in-depth apparently modify the levels of relevant cytokines in the organism to maintain the system homeostasis. Our results suggested that XLZXT might treat DSS-induced UC by repairing the intestinal mucosa barrier, regulating the TLR4/MyD88/NF-κB p65 signaling pathway, and restoring gut microbiota balance.Graphical Abstract: Keywords: ulcerative colitis, TCM, TLR4/MyD88/NF-кB p65 signaling pathway, gut microbiota